Oxford international primary english student book for grade 5 - Barber, Alison (Karachi: Oxford University Press., 2022)
The Oxford International Primary English: Student Book for Grade 5 builds on previous learning, enhancing students' language skills through more complex reading, writing, and comprehension tasks. It introduces students to a wider range of literary forms, including myths, biographies, and reports, while encouraging critical thinking and creativity. The book focuses on refining grammar, punctuation, and spelling, as well as improving writing techniques like narrative structure and persuasive arguments. With a diverse selection of global texts and themes, the book fosters cross-cultural understanding and effective communication, preparing students for more advanced English studies.